Prevalence of social anxiety disorder and its determinants among undergraduate medical students of East Delhi - ., Preeti; Das, Parnava (International Journal Of Community Medicine And Public Health, 2019)
Background: Social anxiety disorder (SAD) is a persistent fear of situations where a person is exposed to a possibility of being under scrutiny. This may lead to decreased academic performance which in turn can lead to depression and suicidal tendencies. Thus, medical students are more vulnerable since they are subjected to stress and academic pressure. The objective of the study was to find out the prevalence and determinants of SAD among medical undergraduate students. Methods: This was a cross-sectional descriptive study done among 404 undergraduate students of a Medical College in east Delhi. Data was collected using a questionnaire containing sociodemographic details and Social interaction anxiety scale (SIAS). Data analysis was done by MS Excel and SPSS 20.0 using frequencies, chi squared test and multiple logistic regression. Results: The mean age of the participants was 20.7 years with 75% males and two-third belonging to upper class. It was found that 12.62% of the study participants were having social phobia and 5.95% were having social anxiety. The determinants found to be significant by univariate analysis were language barrier, body image perception, facial appearance perception and academic performance satisfaction. However, after applying multiple logistic regression it was found out that language barrier (OR-4.36, 95% CI=1.567-12.165, p=0.005) and facial appearance perception (OR-2.98, 95% CI=1.206-7.375, p=0.018) were the main determinants of SAD. Conclusions: Early detection and appropriate intervention needs to be done among the students as they are the most vulnerable and most malleable.